CGIAR Gender Equality in Food Systems Research Platform Proposal Resubmission - CGIAR GENDER Platform (CGIAR GENDER Impact Platform, 2019)
Impactful gender research within CGIAR is a precondition to achieving its mission of enabling people, especially women, to better nourish their families, while improving food system productivity and resilience. In the face of climate change and demographic shifts, such research has become more important than ever before, and is now essential for shared economic growth, manage natural resources and improve the lives of women and men. The CGIAR Generating Evidence and New Directions for Equitable Results (GENDER) Platform that we propose will catalyse targeted research on gender equality in agriculture and effectively collaborate with decision-makers to achieve a new normal: a world in which gender equality drives a transformation towards equitable, sustainable, productive and climate-resilient food systems.